Praktikum Gelembung Ajaib Tentang Stabilitas Gelembung Sabun dengan Penambahan Gula pada Kelas III SDN Karangrejo 1 - Nabila Nurfuaida Yahya; Muhammad Suwignyo Prayogo; Anissa Putri Ramadhania (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study investigates the effect of added sugar on the stability of soap bubbles through a hands-on science activity titled “Magic Bubbles” conducted with third-grade students at SDN 1 Karangrejo. The activity was implemented collaboratively, where students observed, experimented, and drew conclusions together under teacher guidance, without the use of individual worksheets. Using a participatory observation method, the research described students’ engagement, reactions, and learning behavior during the process. Findings revealed that soap bubbles containing added sugar demonstrated greater stability and a longer lifespan compared to those without sugar. Students showed high levels of enthusiasm, curiosity, and active participation throughout the experiment. The activity not only fostered engagement but also enhanced students’ gross motor coordination, observation skills, and early scientific reasoning. Furthermore, it encouraged cooperative learning and communication among peers. The results highlight the effectiveness of simple laboratory-based learning as a medium to introduce scientific inquiry at the elementary level. The “Magic Bubbles” activity aligns with the inquiry-based learning approach in science education, emphasizing direct experience, experimentation, and concept discovery through observation and guided reflection. This study demonstrates that contextual, play-based science activities can meaningfully improve motivation and conceptual understanding among young learners.